Comstock Women : The Making Of A Mining Community - Raymond, C. Elizabeth; James, Ronald M. (Ronald Michael), 1955- (Book collections on Project MUSE., 1998)
The conventional view of Virginia City as a ramshackle mining camp populated largely by miners and the businesses - saloons, hotels, brothels- that served their needs obscures a significant and fascinating aspect of its history: it was home to large numbers of women and children. In this provocative and path-breaking collection of essays, noted scholars from several disciplines examine the lives of the women, from all social classes and many ethnicities, who settled on the Comstock Lode and struggled to create a stable community in that transient boomtown setting. The contributors to Comstock Women consider the complexity of women's experiences on the Comstock Lode, combining traditional historical research with demography, ethnic studies, architectural history, material culture, and literary studies, using as many tools as possible to arrive at insights not addressed by earlier histories and the limited primary records. Their conclusions change the way we view the position of Chinese women, the history of prostitution in the district, the economic roles played by women in the mining West, the wide-ranging social impact of such anodynes as opium, and the idea of community in a boomtown environment. A final essay on gender archaeology suggests yet another way to examine the lives of women who left few written records of their lives.